(untitled) (Academicia Globe: Inderscience Research, 2023)
This study measures the level of Estradiol and a number of biochemical variables, including (cholesterol, triglycerides, high-density lipoproteins, low-density lipoproteins,and very low-density lipoproteins). The study also measures the total antioxidant index, as well as the level of malondialdehyde in naturally pregnant women, as well as pregnant women. after taking steroids.